The Queering of Cuban History: Carmelita Tropicana and Memories of the Revolution - Caballero, I. Carolina (Latin American Theatre Review, 2004)
Through the persona Carmelita Tropicana, Alina Troyano explores her Cuban, American, and queer identities by re-writing Cuban history in Memories of the Revolution. Here Troyano queers the heteronormative interpretation of her communities’ past by including alternative sexual and gender representations. Through this political process, Troyano ultimately writes a space for herself within these culture(s). (ICC)